Online reviews and hospital choice - Ian M. McCarthy; Kaylyn R. Sanbower; Leonardo Sánchez Aragón (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2022)
Information problems in health care and the multifaceted nature of hospital quality complicate hospital choice. Online reviews provide an accessible, salient means through which researchers and health care decision-makers can gather information about a hospital's quality of care, and given their increasing popularity, these measures may affect hospital choice and may have implications for hospital prices. Using the universe of hospital Yelp reviews and inpatient claims data for elective procedures in Florida from 2012 through 2017, we exploit exogenous variation in online hospital ratings over time to identify the effect of online reviews on hospital choice. We find that among admissions for elective, inpatient procedures, patients are willing to travel between 5 and 30 percent further to receive care from a hospital with a higher Yelp rating, relative to other hospitals in the market. We also find evidence that higher ratings translate into higher commercial payments from insurers, albeit with relatively modest magnitudes. Our results indicate that novel, accessible sources of quality information have the potential to affect health care decisions, with potential downstream effects on health care prices.
Keywords: 330; quality disclosure; hospital choice; online reviews; hospital prices